(untitled) (ModaPalavra e-periódico, 2025)
This study analyzes the relationship between market demands, fashion trends, and original design innovation in the development of new materials by a company from the textile industry of Santa Catarina. Through a qualitative case study in a textile company in Santa Catarina, documentary analysis was combined with semi-structured interviews with managers from marketing, style, and production areas. The results reveal that the company prioritizes trend anticipation via research platforms and international fairs, aligning the vast majority of its portfolio with market expectations. Creativity emerges in process gaps, such as research trips for references, but encounters structural limitations, like minimum scale requirements for customized orders. Despite investing in technologies and sustainability, innovation is restricted to incremental adjustments. It is concluded that the company operates in a delicate balance, where originality is mediated by power relations in the production chain. The study suggests the creation of internal experimentation programs and partnerships with independent designers to foster creative breakthroughs.